METACOGNITIVE SKILLS ANALYSIS OF STUDENTS IN INTEGRAL CALCULUS PROBLEM SOLVING - Rahmawati, Nurina Kurniasari; Waluya, S B; Rochmad, Rochmad; Hidayah, Isti (Universitas Tanjungpura, 2021)
This study aims to describe the profile of students' metacognitive skills in solving integral calculus problems seen from the aspects of planning, monitoring and evaluation metacognitive skills. The research method used is descriptive qualitative research methods. The subjects in this study were 3rd semester students who had taken courses or were taking calculus II courses for the 2020/2021 academic year which were carried out using purposive sampling technique. In this study, the instrument used was a test to measure the ability in solving integral calculus problems in the form of essay questions, unstructured interview guidelines, documentation and observation. Data were analyzed in three stages, namely reduction, presentation, and conclusion or verification. The results in this study were students with high problem solving abilities had met the indicators of metacognitive skills, namely the planning, monitoring and evaluation stages. Students with moderate problem-solving abilities have only reached indicators of metacognitive skills, namely the planning and monitoring stages, but have not reached the evaluation stage, while students with low problem-solving abilities have not measured metacognitive skills indicators both at the planning, monitoring and evaluation stages. So that students with high problem solving abilities are more likely to have good metacognitive skills, because students with high problem solving abilities are well organized from planning, monitoring to the evaluation stage.